Multicommodity mineral systems analysis highlighting mineral prospectivity in the Halls Creek Orogen - Occhipinti, S.; Metelka, V.; Lindsay, M.; Hollis, Julie; Aitken, A.; Tyler, I.; Miller, J.; McCuaig, T. (Elsevier Science BV, 2016)
Understanding the regional context of mineral prospectivity is essential for opening areas to effective exploration. The Halls Creek Orogen in Western Australia, is one such region. Here we have completed a multi-commodity mineral systems analysis, which we have used as a basis for the production of semi-automated prospectivity models. Known mineral occurrences or deposits formed over a period dominated by the compressional 1865-1850. Ma Hooper and 1835-1805. Ma Halls Creek orogenies, either followed, or preceded by periods of extension. Prospectivity models were built on knowledge-based fuzzy inference networks for seven commodity groups. The work has demonstrated a link between key model components and the propensity of disparate styles of mineral deposits to occur in this region, which has not been documented before. Different tectonic terranes defined as 'zones' in the Halls Creek Orogen are prospective for different commodity groups. A link between major crustal-scale faults or shear zones and the location of known ore deposits and occurrences in the area has been established. Many structures are either newly discovered, or their extension through the upper crust and down to the Moho has just been established. The lithospheric scale of these structurally weak zones would allow fluid migration from within, or below the lower crust. Of these structures, orogen perpendicular (northwest trending) and orogen oblique (north trending) faults are the most influential structures with respect to ore deposition, especially in regions where they intersect each other. The orogen-parallel structures were found to be less important. The crustal-scale architecture of the region and its link to known mineral occurrences suggests that the mineral prospectivity of the Halls Creek Orogen for commodities such as Ni, Cu, PGEs, Au, Pb, Zn and diamonds could be extended beyond known occurrences into the new zones delineated by the prospectivity analysis.